Peculiarity of the charged particles dynamics at the cyclotron resonances - Buts, V.A.; Kuzmin, V.V.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2016)
In this work the analysis was provided of the discrepancy between thresholds for appearance of the chaotic regime in the conditions of cyclotron resonances, obtained by analytical consideration of the particle dynamics, on the one hand, and by numerical investigation, on the other hand. The explanation is given for these threshold discrepancies Oбсуждается расхождение в порогах появления хаотических режимов, которые получены при аналитическом рассмотрении и при численных исследованиях динамики частиц в условиях циклотронных резонансов. Дано объяснение этим расхождениям. Oбговорюється розбіжність у порогах появи хаотичних режимів, які отримані при аналітичному розгляді і при численних дослідженнях динаміки частинок в умовах циклотронних резонансів. Дано пояснення цим розбіжностям.